2017
DOI: 10.5506/aphyspolbsupp.10.977
|View full text |Cite
|
Sign up to set email alerts
|

Decays of Light Mesons Triggered by Chiral Chemical Potential

Abstract: Light meson ( π, σ, a 0 ) properties in the environment with chiral imbalance are analyzed with the help of meson effective lagrangian associated with QCD. New spatial parity violating decays of scalar mesons arise as a result of mixing of π and a 0 mesons under influence of chiral charge density. The pion electromagnetic formfactor gets an unusual parity-odd contribution. Pion effective masses depend on their velocities and may vanish in flight. The possible determination of chiral chemical potential in heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…To increase predictability, we extend the vacuum Chiral Lagrangians [12,13] with phenomenological low-energy structural constants taking into account the chiral medium in the fireball with a chiral imbalance. It is shown that σ-model parametrization of [11] fits well the pion phenomenology at low energies as derived from ChPT.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…To increase predictability, we extend the vacuum Chiral Lagrangians [12,13] with phenomenological low-energy structural constants taking into account the chiral medium in the fireball with a chiral imbalance. It is shown that σ-model parametrization of [11] fits well the pion phenomenology at low energies as derived from ChPT.…”
Section: Introductionmentioning
confidence: 66%
“…Thus a possible experimental detection of chiral imbalance in medium (and therefore a phase with LPB)) in the charged pion decays and vector meson polarizations inside of the fireball can be realized. In our previous papers [7,11,14] we have described a wider class of direct parity breaking, namely, in the framework of linear sigma model with isotriplet scalar (a 0 ) and pseudoscalar (pions) mesons we predict their mixing with generation of ππ and πππ decays of heavier scalar state. As well the independent check of our estimates could be done by lattice computation (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding to the QCD lagrangian the term ∆L q = µ 5 q † γ 5 q ≡ µ 5 ρ 5 , we open the way of accounting for non-trivial topological fluctuations [2] in the nuclear (quark) fireball, which are related to fluctuations of gluon fields. The behavior of various spectral characteristics for light scalar and pseudoscalar (σ, π a , a a 0 ) -mesons by means of the QCD motivated σ model lagrangian was recently derived for SU L (2) × SU R (2) flavor symmetry with an isosinglet chiral chemical potential [3]. It is shown, in particular, that exotic decays of scalar mesons arise due to mixing of π and a 0 meson states in the presence of chiral imbalance.…”
Section: Chiral Imbalancementioning
confidence: 99%
“…A manifestation for LPB in the presence of chiral imbalance in the sector of ρ and ω vector mesons [3] can also happen and in this case the Chern-Simons interaction plays the main role. It turns out [2] that the spectrum of massive vector mesons splits into three components with different polarizations having different effective masses m 2 V,+ < m 2 V,L < m 2 V,− .…”
Section: Conclusion and Prospectsmentioning
confidence: 99%